Pathogen Recognition Receptors: Ligands and Signaling Pathways by Toll-Like Receptors. (16th April 2013) - Sasai, Miwa; Yamamoto, Masahiro
<x xml:space="preserve">Abstract</x> Toll-like receptors (TLRs) play critical roles in host defense against microbes. In the past decade, growing numbers of in vitro, in vivo and in silico studies have been performed and revealed the physiological significance and structural basis of their ligands and signal transduction, which involves various extracellular, membrane-bound, cytoplasmic and nuclear signaling molecules for the activation of TLR signaling. However, negative regulation of TLR-mediated responses is also essential for the prevention of autoimmunity and is mediated by a number of molecules. In this review, we will introduce recent advances in the understanding of TLR biology in terms of their ligands and signaling pathways.